Forms of Expression in The Toraja Language in The Rambu Solo' Ritual in Bontang: A Pragmatic Study - Syaian, Syaian; Hudiyono, Yusak; Mulawarman, Widyatmike Gede (Jurnal Ragam Pengabdian, 2026)
Study This aim For describe form expression in the Rambu Solo' ritual of the community Toraja in Bontang. The Rambu Solo' ritual is ceremony customs death that has mark strong cultural, social and spiritual in life public Toraja. Research This use approach qualitative with method descriptive. Research data in the form of expression language used​ in the Rambu Solo' ritual . Data collected through technique observation, interviews, and documentation. Data analysis was carried out with use approach pragmatics For understand meaning expression based on context its use. Research results show that form expression in the Rambu Solo' ritual includes expression greeting to deceased , expression prayer or introduction spirits going to natural spirit, and expression social to the people who came mourning. Research This show that expression Language in the Rambu Solo' ritual there is function important in maintain mark culture public Toraja.